2012
DOI: 10.1007/s00402-012-1586-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock-wave therapy reduces progression of knee osteoarthritis in rabbits by reducing nitric oxide level and chondrocyte apoptosis

Abstract: ESWT reduced the progression of OA in rabbits. This effect may be related to decreased level of NO and is likely mediated by reduced chondrocyte apoptosis. ESWT may be a useful treatment for knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 23 publications
1
46
1
1
Order By: Relevance
“…Prior studies reported that ESWT has chondroprotective effects in ACLT-induced OA knee in rats [20-22]. Zhao and his colleagues [22] reported that ESWT reduces the progression of knee OA in rabbits by reducing the nitric oxide level and chondrocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies reported that ESWT has chondroprotective effects in ACLT-induced OA knee in rats [20-22]. Zhao and his colleagues [22] reported that ESWT reduces the progression of knee OA in rabbits by reducing the nitric oxide level and chondrocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that application of ESWT to subchondral bone of the proximal tibia shows a chondroprotective effect in the initiation of OA of the knee and induces regression of established OA of the knee in rats [20-22]. ESWT was noted to have multifunctional effects in bone and cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Although proliferative effects were indicated, some studies have reported no significant effects but some of the recent animal experiments have indicated that ESWT application has chondroprotective effects and relieves symptoms such as pain by improving motor functions (21-24). Zhao et al (25) suggested that these effects were due to the inhibition of nitric oxide (NO) release and partial apopytosis. Mayer-Wagner et al (26) reported that ESWT down-regulates Tenascin-C whose expression increases at the superficial layer of the joint cartilage in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Положительное действие ударной волны на соединительнотканные структуры, костную, мышечную и хрящевую ткани [41][42][43][44][45][46][47][48] [50].…”
Section: виды реабилитационной помощи при па-тологиях суставовunclassified